Illness Perceptions Predict Cognitive Performance Validity. (29th April 2018) - Henry, George K.; Heilbronner, Robert L.; Suhr, Julie; Gornbein, Jeffrey; Wagner, Eveleigh; Drane, Daniel L.
Abstract: Objectives: The aim of this study was to investigate the relationship of psychological variables to cognitive performance validity test (PVT) results in mixed forensic and nonforensic clinical samples.Methods: Participants included 183 adults who underwent comprehensive neuropsychological examination. Criterion groups were formed, that is, Credible Group or Noncredible Group, based upon their performance on the Word Memory Test and other stand-alone and embedded PVT measures.Results: Multivariate logistic regression analysis identified three significant predictors of cognitive performance validity. These included two psychological constructs, for example, Cogniphobia (perception that cognitive effort will exacerbate neurological symptoms), and Symptom Identity (perception that current symptoms are the result of illness or injury), and one contextual factor (forensic). While there was no interaction between these factors, elevated scores were most often observed in the forensic sample, suggesting that these independently contributing intrinsic psychological factors are more likely to occur in a forensic environment.Conclusions: Illness perceptions were significant predictors of cognitive performance validity particularly when they reached very elevated levels. Extreme elevations were more common among participants in the forensic sample, and potential reasons for this pattern are explored. ( JINS, 2018, 24, 735–745)